Evaluasi Pelaksanaan Perubahan Kebijakan Jam Kerja Tenaga Kependidikan dengan Pendekatan Teori Penerimaan terhadap Otoritas - Stefanus Khrismasagung Trikusumaadi; Noviana Dewi (Akuntansi Pajak dan Kebijakan Ekonomi Digital, 2025)
Changes in working-hour policies can bring both positive and negative impacts to an organization. At a private university, the implementation of such a policy has generated noticeable reactions among employees, particularly administrative staff who are directly affected by daily operational regulations. This study aims to evaluate the implementation of the revised working-hour policy, specifically how it is understood, practiced, and accepted by administrative personnel. In addition, the study examines the relationship between employees’ acceptance of the policy and Barnard’s theory of acceptance of authority, which emphasizes four conditions that must be met for individuals to willingly comply with directives or regulations. The results show that violations of the working-hour policy fall into the low category at 64%, medium at 24%, and high at only 12%. These findings indicate that the majority of administrative staff still attempt to comply with the policy despite adjustments that may be perceived as burdensome. Among the four conditions supporting compliance according to Barnard, the belief that the policy does not conflict with personal goals was found to have a significant relationship with the level of violation, with a correlation coefficient of 0.304 and a significance value of 0.032. This suggests that the greater the alignment between the policy and individual goals, the lower the likelihood of violation. Future studies are needed to convert violation rates into compliance measures so that the direction of the correlation can be interpreted more accurately.